2016
DOI: 10.3109/0886022x.2015.1136894
|View full text |Cite
|
Sign up to set email alerts
|

Human embryonic mesenchymal stem cells alleviate pathologic changes of MRL/Lpr mice by regulating Th7 cell differentiation

Abstract: Recent evidence indicates that mesenchymal stem cells (MSC) derived from early embryonic tissues have better therapeutic ability as compared with adult tissue-derived stem cells. In the present study, we transplanted human early embryonic MSC (hMSC) into MRL/Lpr mice via tail vein injection to observe the therapeutic efficacy of hMSC and their impact on T helper 17 (Th17) cell differentiation in MRL/Lpr mice. Animals in hMSC treatment group received hMSC (1 Â 10 6 /200 mL) via the tail vein at the age of 16 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…MSC transplantation has been considered an ideal treatment method for LN due to their plentiful sources, low immunogenicity, and lack of ethical issues. Studies have demonstrated that xenogeneic MSC administration leads to improvement of the renal injury in MRL/lpr mice [1922]. Choi, E. W. et al [5] showed that xenogeneic transplantation of adipose tissue-derived MSCs initiated a strong humoral immune response, improved the symptoms of LN in the (NZB × NZW) F1 mice, and had many advantages, such as convenient and abundant sources and ease of isolation, culture, amplification, and purification.…”
Section: Discussionmentioning
confidence: 99%
“…MSC transplantation has been considered an ideal treatment method for LN due to their plentiful sources, low immunogenicity, and lack of ethical issues. Studies have demonstrated that xenogeneic MSC administration leads to improvement of the renal injury in MRL/lpr mice [1922]. Choi, E. W. et al [5] showed that xenogeneic transplantation of adipose tissue-derived MSCs initiated a strong humoral immune response, improved the symptoms of LN in the (NZB × NZW) F1 mice, and had many advantages, such as convenient and abundant sources and ease of isolation, culture, amplification, and purification.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies [11,13,16,[22][23][24]37] were included to assess the effects of MSC on BUN. The results showed that the difference in BUN levels between the MSC group and the control group was notable (OR = − 14.57, 95% CI − 20.50, − 8.64; P < 0.00001; Table 2), and the MSC group had lower levels of BUN.…”
Section: Assessment Of Bunmentioning
confidence: 99%
“…The albumin levels were also detected, and two studies [10,23] were recruited. The results showed that the MSC group had higher levels of albumin, and the difference in albumin levels between the MSC group and the control group was notable (OR = 7.22, 95% CI 3.74, 10.69; P < 0.0001; Table 2).…”
Section: Assessment Of Albuminmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same study [42], TGF-β was shown to stimulate Tregs both in vitro and in vivo in SLE patients. In addition, TGF-β is involved in inhibiting the immune response by suppressing dendritic cell (DC) maturation [43] and T-helper 17 (Th17) cell generation [44]. MSCs secrete metalloproteinases (MMPs) that are able to halt CC (C–C motif) chemokines such as CCL2 (targeting chemokine (C–C motif) ligand 2).…”
Section: Molecules and Enzymes Of Mscs Secretomementioning
confidence: 99%